Framework features enabling faster establishment and better management of privately protected areas in New South Wales, Australia - Elton, Paul; Fitzsimons, James A. (Frontiers in Conservation Science, 2023)
In response to the Convention on Biological Diversity's Kunming-Montreal Global Biodiversity Framework, Australia has committed to protecting 30% of lands and oceans for nature conservation by 2030. Privately protected areas are vital to meeting this target and establishing an ecologically representative and well-connected National Reserve System on land in Australia. As a federated nation, most public and privately protected areas (especially conservation covenants) are established under state or territory (i.e. subnational) legislation, as opposed to national legislation. This paper conducts a review of changes in policy and practice for private land conservation in the state of New South Wales (NSW) that has led to a marked acceleration in the establishment of privately protected areas since 2017. The historical average rate at which privately protected areas were being established in NSW under various schemes prior to the changes in 2017 was about 50 agreements and 12,000 hectares per annum. The new Biodiversity Conservation Act 2016, the Biodiversity Conservation Trust of NSW (BCT), and increased NSW Government funding commenced in August 2017. Since then, the rate of establishment of privately protected areas has accelerated to more than 100 agreements and 45,000 hectares per annum. Not only has the rate of establishment more than tripled (by area) but many more PPAs are being established in higher priority bioregions, and the BCT is now able to provide better financial and technical support to extant PPAs, leading to better conservation outcomes overall. Key changes that have strengthened the framework for establishing and managing privately protected areas in NSW include a guide for strategic investment; institutional arrangements that foster effective governance, trust and transparency; substantive NSW Government funding; an accumulating endowment fund model; in-perpetuity payments; and faster and more targeted delivery mechanisms. The paper highlights features that could be adopted in other jurisdictions in Australia to support the vital role that privately protected areas must play in achieving commitments to nature conservation.